2019
DOI: 10.1111/hiv.12830
|View full text |Cite
|
Sign up to set email alerts
|

Promoting oral HIV self‐testing via the internet among men who have sex with men in China: a feasibility assessment

Abstract: ObjectivesThe HIV prevalence among Chinese men who have sex with men (MSM) is high, while the HIV testing rate is low. HIV self-testing (HIVST) is a promising means of scaling up HIV testing among MSM in China, as the ability to test in private is appealing to many individuals. We evaluated the feasibility of promoting oral HIVST via the internet in the MSM population. MethodsFrom April 2013 to April 2014, MSM in two major cities in China were recruited for an observational study with assessment at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Half of all studies (54%, 25/46) deployed website-based interventions. Results were largely in favor of digital strategies including e-testing websites [15] , [16] , [17] , [18] , [19] , study websites [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , online counselling [33] , [34] , [35] , [36] , [37] , [38] , and chatbots [39] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Half of all studies (54%, 25/46) deployed website-based interventions. Results were largely in favor of digital strategies including e-testing websites [15] , [16] , [17] , [18] , [19] , study websites [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , online counselling [33] , [34] , [35] , [36] , [37] , [38] , and chatbots [39] .…”
Section: Resultsmentioning
confidence: 99%
“…Eight (32%, 8/25) studies assessing web-based interventions reported acceptability outcomes [ 18 , 21 , [26] , [27] , [28] , [29] , 37 ]. Willingness to use web-based HIVST interventions (61%−79%) [ 18 , 21 , 26 , 27 , 29 , 37 , 38 ] and ease of use (97%) [28] was high across studies, and among high-risk groups such as MSM, transgender women, men with multiple sexual partners, and men who were less likely to have previously sought out HIV testing [ 28 , 29 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2013, the HIV testing rate of MSM in China has shown an upward trend ( Wu et al, 2021 ). However, HIV testing in China’s MSM is still at a low level ( Wang et al, 2020 ). About 50% to 60% of MSM had not been tested for HIV in the past year ( Ren et al, 2017 ; Tang & Lyu, 2021 ; Wu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIV self-testing (HIVST), conducted by individuals at home or in other private venues without specialized training, has high acceptability and accuracy among MSM in China. 9,10 It could increase HIV testing frequency among MSM in China. 11 Currently, HIVST is implemented and promoted nationwide in China, but PrEP/ PEP has yet to be widely acknowledged.…”
Section: Introductionmentioning
confidence: 99%